The correlation between double taxation conventions, tax compliance, and tax evasion. Empirical evidence from OECD countries - Dumiter, Florin Cornel (Technological and Economic Development of Economy, 2023)
The topics approached in this paper are of interest due to the divergent opinions that emerged in the media academics and practitioners concerning how the double taxation conventions are constructed, the official language in which an international convention must be written, and their de facto application, both in bilateral situations and among triangular or multilateral situations. To be more specific, the way in which double taxation conventions are constructed, signed, and implemented will generate changes in the level of direct taxes, at a certain time interval, both economically and legally with a special focus on tax compliance and tax evasion. Consequently, tax compliance is very important because of the behavior of the taxpayer and the willingness to pay taxes both on the national and international levels. Moreover, tax evasion is a serious problem that creates distortion and undermines worldwide trade and commerce. In this article, it is approached the complex relationship between double taxation conventions, tax compliance, and tax behavior in order to establish the connections and interactions between these three important aspects. The objective of this study is o evaluate and assess the interconnections between these three variables. The empirical study is revealed for selected comprehensive OECD countries with a panel data approach and with modeling techniques using Python software. The conclusions of this study reveal that between double taxation conventions, tax compliance, and tax evasion there is manifested strong connections both positive and negative, aspects highlighted by the empirical results, because the complex relationship manifested in practice regarding the stipulation of the law, the financial aspects and the application of fiscal policy, both on national and international levels.